2022
DOI: 10.3855/jidc.16998
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome after COVID-19 vaccination: report of two cases from Vietnam

Abstract: Coronavirus disease 2019 (COVID-19) was declared a pandemic by the World Health Organization in March 2020 and since then it has spread to almost every country around the world. Vaccines against COVID-19 are considered an essential measure to curb this pandemic. However, side effects, including local and systemic reactions, after administering the COVID-19 vaccine have been defined, and some side effects have been reported. We present two cases of Guillain-Barré Syndrome (GBS) after receiving the ChAdOx1 nCoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Under this scenario, autoantibodies, induced by an external factor, target epitopes on peripheral nerves and induce axonal damage and neuronal demyelination ( 46 , 47 ). Therefore, some authors suggested that GBS following the administration of the COVID-19 adenoviral vector vaccine is due to cross-reaction between generated antibodies against SARS-CoV-2 spike protein and neuronal proteins ( 48 50 ). Moreover, using a bioinformatic approach the molecular mimicry was predicted between spike protein epitopes and sequences of eight proteins involved in biological processes related to myelin and axons, i.e., neural cell adhesion molecule, receptor-type tyrosine-protein phosphatase zeta, teneurin-4, receptor tyrosine-protein kinase erbB-2-, integrin alpha-X, integrin beta-1, attractin, and myelin-associated glycoprotein ( 51 ).…”
Section: Evaluating the Hypothesesmentioning
confidence: 99%
“…Under this scenario, autoantibodies, induced by an external factor, target epitopes on peripheral nerves and induce axonal damage and neuronal demyelination ( 46 , 47 ). Therefore, some authors suggested that GBS following the administration of the COVID-19 adenoviral vector vaccine is due to cross-reaction between generated antibodies against SARS-CoV-2 spike protein and neuronal proteins ( 48 50 ). Moreover, using a bioinformatic approach the molecular mimicry was predicted between spike protein epitopes and sequences of eight proteins involved in biological processes related to myelin and axons, i.e., neural cell adhesion molecule, receptor-type tyrosine-protein phosphatase zeta, teneurin-4, receptor tyrosine-protein kinase erbB-2-, integrin alpha-X, integrin beta-1, attractin, and myelin-associated glycoprotein ( 51 ).…”
Section: Evaluating the Hypothesesmentioning
confidence: 99%